Attosecond pulse generation isolated with an asymmetric polarization gating. Issue 10 (17th June 2017) - Chen, Gao; Cunningham, Eric; Chang, Zenghu
Abstract: High harmonics generated using the polarization gating technique are simulated under the strong-field approximation for the cases of equal and unequal ratios between the amplitudes of the two counter-rotating pulses. The effect of the field asymmetry is observed on the high harmonic yield and cut-off in the frequency domain and on the attosecond pulse duration and satellite peak contrast in the time domain. The case where the strong pulse comes later is more favourable in terms of generating a higher cut-off and a shorter pulse duration. It is predicted that thin metal filters can reduce the impact of satellite pulses while simultaneously reducing the pulse duration.